The effect of combined red, blue, and near-infrared light-emitting diode (LED) photobiomodulation therapy on speed of wound healing after superficial ablative fractional resurfacing - Soliman, John; Elsanadi, Rachel; Messele, Feben; Kelly, Kristen M. (Lasers in medical science, 2024)
Objective of the study is to assess the effects of wound healing with a commercially available light emitting diode (LED) photo biomodulation (PBM) device that emits three wavelengths (465, 640 and 880nm) after ablative fractional laser (AFL) treatment to healthy skin on the bilateral inner biceps. We conducted a prospective intraindividual randomized controlled study with 25 volunteers. AFL treatment was performed on healthy skin of the bilateral inner biceps. Subjects applied the LED light device for 30 min to the assigned bicep 3 times a week over 4 weeks, beginning on day 0. Subjects were followed up on days 2, 4, 6, 9, 13, 20 and 27 for treatment with the PBM device, clinical digital photography of the test and control sites, and in-person subject assessment, with follow ups on days 34 and 55 for clinical photography and assessment. Three blinded evaluators were asked to determine which bicep healed faster between day 0 to day 13. Pain, discomfort, and itch were also assessed. The three blinded evaluators chose the treatment arm as the faster healed arm in greater than 50% of the images, although the results were not statistically significant. There was no statistically significant difference between test and control arms in terms of pain, discomfort and itch. In conclusion, PBM therapy has the potential to improve wound healing. In this study, a three wavelength PBM device resulted in some subjects achieving faster healing after AFL but the results were not statistically significant.